2020
DOI: 10.1093/hcr/hqaa004
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis on Mediated Contact and Prejudice

Abstract: This paper presents a meta-analysis of 79 cases (N = 21,857) testing the effectiveness of mediated intergroup contact on prejudice. Positive mediated contact decreased (r = −.23; 95% CI, −.29 to −.17), whereas negative mediated contact increased prejudicial attitudes (r = .31; 95% CI, .24 to .38) and intergroup anxiety and empathy were both significant mediators of these relationships. Furthermore, the data revealed no significant differences between parasocial and vicarious effects, positive and negative medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 65 publications
1
58
0
1
Order By: Relevance
“…Vast empirical evidence shows that parasocial contact affects perceptions of a disliked outgroup. A recent meta‐analysis on mediated contact reported 56 studies, which examined both negative and positive parasocial contacts with different minority groups and their effects on prejudice (Banas et al., 2020). The paper cited numerous studies showing an improvement in attitudes upon positive exposure in videos toward immigrants, LGBTQ individuals, Muslims, African Americans, people with mental illnesses, and with STDs.…”
Section: Television Changing Viewsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vast empirical evidence shows that parasocial contact affects perceptions of a disliked outgroup. A recent meta‐analysis on mediated contact reported 56 studies, which examined both negative and positive parasocial contacts with different minority groups and their effects on prejudice (Banas et al., 2020). The paper cited numerous studies showing an improvement in attitudes upon positive exposure in videos toward immigrants, LGBTQ individuals, Muslims, African Americans, people with mental illnesses, and with STDs.…”
Section: Television Changing Viewsmentioning
confidence: 99%
“…Multiple research projects indicated that modeling of positive intergroup interactions results in the vicarious learning of positive diversity attitudes. The aforementioned meta‐analysis of mediated contact listed 22 studies featuring vicarious intergroup contact (Banas et al., 2020). The cited studies reported an improvement in attitudes toward immigrants, LGBTQ people, Muslims, and African Americans, thus proving that vicarious intergroup contact on television affects the audiences' perceptions.…”
Section: Television Changing Viewsmentioning
confidence: 99%
“…Spurred by the literature demonstrating the association between face‐to‐face cross‐group interactions (or direct intergroup contact) and reduced prejudice, scholars began to explore indirect forms of intergroup contact (i.e., those that do not require two individuals to interact with one another in close physical proximity; Harwood, 2010). The efficacy of many indirect contact strategies have now been established (see White et al., this volume), including imagined contact (Miles & Crisp, 2014), extended contact (Zhou et al., 2019), representations of outgroups in the media (Banas et al., 2020), and computer‐mediated contact (White et al., 2020).…”
Section: Technique Research Benefits Applied Benefits Constraintsmentioning
confidence: 99%
“…In an intergroup context, research has shown that watching an intergroup encounter ( vicarious contact; Mazziotta et al., 2011), viewing a person from an outgroup ( mediated contact; Park, 2012), or forming a perceived connection with an outgroup character ( parasocial contact; Schiappa et al., 2006) can all reduce intergroup prejudice (Banas et al., 2020). Evidence also indicates that intergroup encounters are shaped by what individuals have previously learned about the outgroup (MacInnis & Page‐Gould, 2015; O'Donnell et al., 2019; Paolini et al., 2016).…”
Section: Contextualizing Intergroup Contactmentioning
confidence: 99%
“…Moreover, it is hypothesized that girls will show more positive attitudes toward children with autism compared to boys (H3) because they might be brought up to take care of others more than boys are (Feingold, 1994;Morawska, 2020;Su et al, 2009). Finally, intergroup literature has shown that regular contact improves attitudes toward disability (Banas et al, 2020;Schwab, 2017;Vignes et al, 2009). Consequently, it is hypothesized that children who are more familiar with disability and especially with autism will report more positive attitudes toward children with autism compared to children who are not familiar with disability/autism.…”
Section: Overview and Hypothesesmentioning
confidence: 99%